Bentonite-Amended Geo-Polymerised Fly Ash-GGBS Mixture for Waste Containment Applications - Sagiri Sivasai Saranya; Maya Naik; Puvvadi Sivapullaiah (International Islamic University Malaysia Engineering Journal)
The reuse of Fly Ash (FA) with the optimum amount of Ground Granulated Blast Furnace Slag (GGBS) polymerized with an alkali solution for the construction of barriers for waste containment and vertical cutoff walls for the contaminated ground is explored in this study. For this, detailed strength and permeability tests have been conducted on different ratios of FA and GGBS compacted and cured for up to 28 days. Compacted samples of FA and GGBS mixtures, at an optimal ratio of 40:60, were polymerized with sodium hydroxide alkali solution up to 5 molar concentration, as the effectiveness of polymerization varies with alkali concentration. The significant increase in compressive strength is attributed to pozzolanic reactions, whereas the increase in tensile strength is due to the polymerization of the components of the mixtures. Geopolymerisation is done through the incorporation of alkali and is known to enhance pozzolanic activity by converting part of silica to reactive silica, producing more pozzolanic compounds and part modification of pozzolanic reaction compounds. To optimize the increase in compressive strength and the percent reduction in tensile strength, the maximum concentration of alkali is restricted to 5 M. To reduce the permeability for their application in the construction of the barrier, a 5% bentonite, in addition to the optimum FA-GGBS mixture, is considered, as its high specific surface and negative charges can retain ionic contaminants such as heavy metals. Both compressive and tensile strength increased over curing, and permeability decreased. The retention capacity of selected heavy metal (lead and nickel) ions is due to their precipitation in the voids of the barrier materials.